PTU-063 Assessment of Sleep Impairment in Patients With Crohn'S Disease: Results from the Ustekinumab Certifi Study. (4th June 2013) - Gasink, C; Chan, D; Gao, L-L; Schenkel, B; Han, C
Abstract : Introduction: To describe the extent of sleep impairment reported in CERTIFI (Ph2 evaluating UST in inducing & maintaining clinical response & remisison)using Jenkins Sleep Evaluation Questionnaire (JSEQ) & establish a clinically meaningful improvement threshold for JSEQ. Methods: Pts with moderate-to-severe CD(CDAI ≥220 & ≤450) who had previously failed or were intolerant to ≥1 anti-TNF were randomised to PBO/UST induction at wk0. Primary endpt was clinical response (≥100-pt reduction in CDAI from BL) at wk6. Sleep impairment assessed using JSEQ (total score 0–20; higher scores indicate greater sleep impairment) at BL&wk6. Relationships between BL sleep impairment, clinical disease activity (CDAI), & HRQoL impact(IBDQ) evaluated using Pearson correlation. Clinically meaningful improvement threshold of JSEQ was established with the anchor-based [clinical response by reduction in CDAI of ≥70-pt or clinically meaningful improvement (≥16-pt) in IBDQ] & distribution-based (change by one-half of the standard deviation [SD] of BL JSEQ score) methods. Prop of pts who achieved clinically meaningful improvements in JSEQ at wk6 was determined & compared. Results: At BL, both grps(n = 526) experienced similar degree of moderate sleep impairment, with JSEQ scores (mean±SD) of 11.0 ± 4.30(PBO)&11.0 ± 4.59(UST), resp. About 60% were "waking up feeling tired and worn out"; about 30–35% of pts had trouble falling asleep, staying asleep, & woke up several times during the night for 15–30 days in the previous month. At BL, JSEQ was correlated with CDAI (r = 0.19, p < 0.0001)&IBDQ(r = –0.39, p < 0.0001). Using the anchor-based method, pts who achieved vs didn't achieve clinically meaningful improvements in CDAI or IBDQ at wk6 vs BL, reported improvements(mean±SD)from BL in JSEQ of –2.52 ± 4.43vs-0.58 ± 3.51 & –2.68 ± 4.16vs-0.16 ± 3.45, resp. Using distribution-based method, the JSEQ clinically meaningful improvement threshold was 2.25(SDof BL JSEQ = 4.50). 2 potential thresholds for clinically meaningful improvement in JSEQ (eg.reduction of > 2 or > 3 points from BL JSEQ score at wk6) were derived. More pts who received UST induction achieved both thresholds at wk6(Table). Conclusion: Pts experience significant sleep problems as measured by JSEQ; magnitude of impairment correlates with disease activity. Both anchor- &distribution-based methods derive similar thresholds representative of clinically meaningful improvements in JSEQ. UST induction resulted in a greater proportion of pts achieving clinically meaningful improvements in sleep impairments. Disclosure of Interest: C. Gasink Employee of: Janssen R&D, LLC, D. Chan Employee of: Janssen R&D, LLC, L.-L. Gao Employee of: Janssen R&D, LLC, B. Schenkel Employee of: Janssen Scientific Affairs, LLC, C. Han Employee of: 3. Janssen Pharmaceutical Services